2013
DOI: 10.1088/0957-4484/24/4/045303
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial top-gated atomic-scale silicon wire in a three-dimensional architecture

Abstract: Three-dimensional (3D) control of dopant profiles in silicon is a critical requirement for fabricating atomically precise transistors. We demonstrate conductance modulation through an atomic scale 3 nm wide δ-doped silicon-phosphorus wire using a vertically separated epitaxial doped Si:P top-gate. We show that intrinsic crystalline silicon grown at low temperatures (∼250 °C) serves as an effective gate dielectric permitting us to achieve large gate ranges (∼2.6 V) with leakage currents below 1 pA. Combining sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…A rather unique branch of the 2D material family are ultrashallow, high-density, doping profiles in semiconductors, so-called δ-layers. In particular, phosphorus δ-layers in silicon (Si:P δ-layers) combined with atomically precise lithography have led to recent technological successes towards scalable qubit architectures [5][6][7][8]. It has been demonstrated that P donors, which can act as qubits, in Si have long spin lifetimes [9,10] which are essential for spin-based quantum calculations.…”
mentioning
confidence: 99%
“…A rather unique branch of the 2D material family are ultrashallow, high-density, doping profiles in semiconductors, so-called δ-layers. In particular, phosphorus δ-layers in silicon (Si:P δ-layers) combined with atomically precise lithography have led to recent technological successes towards scalable qubit architectures [5][6][7][8]. It has been demonstrated that P donors, which can act as qubits, in Si have long spin lifetimes [9,10] which are essential for spin-based quantum calculations.…”
mentioning
confidence: 99%
“…It is essential that this encapsulation layer be crystalline in order to achieve optimum dopant activation and carrier densities. Furthermore, high quality low temperature Si overgrowth not only improves the performance of 2D patterned devices, but also plays an important role in extended applications involving 3D architectures [2],[36],[37] .…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in atomic scale patterning of phosphorus dopants on hydrogen terminated Si (100) surfaces using STM lithography have resulted in a variety of atomic scale devices, including wires [1],[2] , quantum dots [3],[4] and single atom transistors [5] . As the building blocks for the Si based Kane quantum computer [6],[7],[8] , most of these approaches rely on patterning a hydrogen resist layer [9],[10] and selectively adsorbing dopant atoms in areas defined by lithographic patterns [11],[12] .…”
Section: Introductionmentioning
confidence: 99%
“…Nanosilicon may also acquire quantum mechanical properties at small quantum dot sizes [42,164,166,167], a feature that may help account for certain other observations in the homeopathic drug development research literature [147,148,168]. Doping of the nanosilicon and nanosilica by the medicine source material and other trace contaminants in solution during early preparation steps [9] may add more memory and amplification mechanisms [164,169,170].…”
Section: Stochastic Resonance Peakmentioning
confidence: 99%